Corporate Bankruptcy and Financial Restructuring - Fahdil, Husam Nawfal; Abdulkarim, Maysoon Abdulghaini; Mohamed, Jassim; Allah, Eman Abdel Moneim Mal (Journal of Ecohumanism, 2024)
Background: The increasing intricacies of corporate bankruptcy and financial restructuring in the global economy highlight the importance of comprehending the procedures and results for distressed organizations. The article focuses on the lack of information and action regarding the recovery of financially struggling companies, acknowledging the significance of this matter for scholars, professionals, and policymakers. Objective: This study aims to analyze the complexities of corporate bankruptcy, emphasizing the legal, financial, and operational obstacles and solutions used by corporations to manage financial difficulties. The goal is to provide a detailed examination of the methods and institutions that support business recovery and the impact on different stakeholders. Methodology: Utilising a qualitative research approach, the article conducts a thorough examination of legal texts, empirical case studies, and relevant datasets related to corporate bankruptcy and restructuring. The goal is to clarify the functions of various bankruptcy processes, including debtor-in-possession financing, and alternatives like out-of-court restructuring. Results: The results emphasize the many tactics used by corporations to reduce financial hardship, focusing on the interconnection between legal regulations, financial tools, and stakeholder involvement. The study reveals the key aspects that impact the effectiveness of restructuring initiatives, such as protecting stakeholder interests, ensuring employee well-being, and adhering strictly to legal obligations. The article provides information on the difficulties and factors that help with restructuring procedures, giving a better understanding of the practical elements involved in managing corporate bankruptcy. Conclusion: The article enhances comprehension of corporate bankruptcy and financial restructuring, emphasizing the need for a comprehensive strategy that focuses on legal compliance and stakeholder interests. This emphasizes the consequences for the continuous recovery of companies in an uncertain economic setting and proposes avenues for future study and application in the field of corporate financial revitalization. The results support the need for deliberate and well-informed decision-making to improve the resilience and recovery of struggling organizations.